High frequency monitoring reveals fine scale spatial and temporal dynamics of the deep chlorophyll maximum of a stratified coastal lagoon. (5th March 2019) - de Eyto, Elvira; Kelly, Sean; Ryder, Elizabeth; Dillane, Mary; Archer, Lorraine; O'Cathain, Donncha; Daly, Sile; Lyons, Kieran; Obrador, Biel; Brentrup, Jennifer; Naumoski, Andreja; Poole, Russell; et al.
Abstract: Coastal lagoons are a dynamic habitat, with varying marine and freshwater inputs determining the presence and extent of stratification, and the physical and chemical environment of the epi- and hypolimnion. As a result, the biotic assemblages that thrive in such environments are a diverse mix of species, with wide ranges of tolerances. While annual succession and vertical distribution of phytoplankton assemblages in marine and freshwater ecosystems are well documented, few data are available which describe the spatial and temporal variability of phytoplankton in coastal lagoons, even though these are a protected habitat under the European Union's Habitat Directive. In this study, high frequency monitoring (HFM) of chlorophyll fluorescence (ChlF) using a vertical profiling sonde was used to describe the variation in algal biomass over six annual cycles and through the water column of Lough Furnace, a perennially stratified coastal lagoon on the west coast of Ireland. Spot sampling, and species enumeration of phytoplankton were used to confirm the patterns observed in the fluorescence data, which indicated a general pattern of increasing biomass starting in spring, and a deepening of the deep chlorophyll maximum (DCM) over the summer. Typical of a stratified system, the DCM was often situated below the surface mixed layer, in saline hypoxic water. The best predictors of daily maximum ChlF were the depth of the surface mixed layer and daily solar radiation. We conclude that HFM allows an unprecedented glimpse into the substantial variability and complexity of phytoplankton distributions, a key biotic variable. Graphical abstract: Image 1